2001
DOI: 10.1016/s0886-3350(01)01089-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of corneal thickness measurements using ultrasound and Orbscan slit-scanning topography in normal and post-LASIK eyes

Abstract: Central corneal thickness measurements were, on average, 28 microm higher with the Orbscan than with the ultrasound pachymeter in normal eyes and 13 microm lower in post-LASIK eyes. The degree of variability within each group indicated that these 2 techniques are not clinically comparable, precluding interchangeable use of their data in planning or assessing corneal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
73
1
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(82 citation statements)
references
References 10 publications
3
73
1
5
Order By: Relevance
“…Although the accuracy, precision, and repeatability of the Orbscan system has been accepted for use in research, it is recognized that it overestimates CCT compared to the more commonly used technique of ultrasound pachymetry. 10,31,32 The current study has taken this into account by applying the standard acoustic correction factor. 13 The repeatability of Orbscan pachymetry has been demonstrated to be approximately 2 mm 33 to 5 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Although the accuracy, precision, and repeatability of the Orbscan system has been accepted for use in research, it is recognized that it overestimates CCT compared to the more commonly used technique of ultrasound pachymetry. 10,31,32 The current study has taken this into account by applying the standard acoustic correction factor. 13 The repeatability of Orbscan pachymetry has been demonstrated to be approximately 2 mm 33 to 5 mm.…”
Section: Discussionmentioning
confidence: 99%
“…The pachymetric values variation, observed in both patients groups, remained within the normal limits for the test (24)(25)(26) (Table 1).…”
Section: Discussionmentioning
confidence: 54%
“…The normal healthy cornea is usually prolate, but after myopic LASIK the corneal curvature is altered and tends to become oblate. 2 The reconstruction algorithms, using lower order polynomials, which create elevation data in the Orbscan-II may be properly designed in a normal corneal surface, but they might be ineffective in a post-LASIK corneal surface. 2 The main limitation of the current study is that the reason for the variability between measurements showed a wide distribution between methods was not completely addressed, although it can be explained by the measurement repeatability of Orbscan-II being generally lower than that of Topcon NCSM in postmyopic LASIK patients.…”
Section: Discussionmentioning
confidence: 99%
“…2 The reconstruction algorithms, using lower order polynomials, which create elevation data in the Orbscan-II may be properly designed in a normal corneal surface, but they might be ineffective in a post-LASIK corneal surface. 2 The main limitation of the current study is that the reason for the variability between measurements showed a wide distribution between methods was not completely addressed, although it can be explained by the measurement repeatability of Orbscan-II being generally lower than that of Topcon NCSM in postmyopic LASIK patients. 35 In addition, this study included only patients who had undergone LASIK to treat myopia, and, therefore, the conclusions cannot be applied to patients with hyperopia, in whom the postoperative corneal shape is more prolate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation